The Study of Hematology in Commercial Broiler Chickens of Cobb 500, Ross 308, and Arbor Acres Plus - Kongpechr, Saijai; Sukon, Peerapol; Sohsuebngarm, Damnern (Journal of Mahanakorn Veterinary Medicine, 2021)
The objectives of this study were to establish reference values of packed cells volume (PCV) or hematocrit and to compare other hematological values in three breeds of commercial broiler chickens popular raised in Thailand (Cobb 500, Ross 308 and Arbor Acres Plus) during day old chick to 35 days of age. A total of 1800 broiler chickens were used for this study. At day old chick, 7, 14, 21, 28 and 35 days of ages, 300 chickens (100 for each breed with 50 male and 50 female) were randomly selected from the commercial broiler houses. A blood sample was collected from metatarsal vein in a day old and 7 day old chicks and from cutaneous ulnar vein from 14 day old chicks or older. The PCV was determined from all 1800 chickens. Other hematological values (Red Blood Cells; RBC, White Blood Cells; WBC, heterophil, lymphocyte, monocyte and basophil) were determined from 300 chickens (10 chickens from each age (except 7 days of age)/breed/sex). Analysis of variance and simple linear regression were used for data analysis. The results showed that a trend of the PCV slightly increased with age of the chickens. The average PVC values in male of Cobb 500, Ross 308 and Arbor Acres Plus broiler chickens from DOC to 35 days were 24.68 – 32.66 %, 22.61-33.41% and 22.71-33.72 %, respectively. Those in female were 21.67-33.05 %, 24.71-33.76 % and 24.65-33.29 %, respectively. The average RBC counts of Cobb 500, Ross 308 and Arbor Acres Plus broiler chickens from DOC to 35 days are 1.67-2.62X106cells/µl, 1.52-2.45X106cells/µl and 1.49-2.51X106cells/µl, respectively in male and 1.50-2.79X106cells/µl, 1.42-2.51X106cells/µl and 1.48-2.61X06cells/µl, respectively in female. The average WBC counts were 1.41-12.39X103cells/µl, 1.10-13.44X103cells/µl and 1.95-11.89X103cells/µl, respectively in male and 1.23-13.60X103cells/µl, 0.94-10.23X103cells/µl and 1.96-10.25X103cells/µl, respectively in female. In conclusion, the reference values of PCV in commercial broiler chickens of are established from this study.